Optimierte Netzverträglichkeit von Gleichstrom-Schnellladesystemen durch aktive Netzbeeinflussung - Krasselt, Peter Florian (KIT Scientific Publishing, 2016)
The roll-out of a high-performance DC electric vehicle supply equipment infrastructure is a key factor for the success of electric mobility. This work enhances existing control schemes for active rectifiers utilized in charging systems, resulting in minimized requirements for network connection. In addition, active power quality filtering is achieved. The proposed control concept is experimentally validated using a fast charger system.